Acomparative study of the effect of Cisplatin and Albendazole in the Echinococcosis infection in vivo and in vitro and study of the associated histological changes - Abd-Al Rhman, Muslem (University of Thi-Qar Journal of Science, 2012)
The present study is included evalution activity cisplatine and albendazole in killing of protoscolices isolation from sheep liver In vitro, also studying pathogenic effects on the liver and kidney and activity of them on hydatid cyst number. Also this study improved capability of cisplatin and albendazole to enter the hydatid cyst.This study appeared that cisplatin has ahigh activity in killing of protoscolices In Vitro which reached for percentage (51.8 , 92.8) % after (1,2) weeks subsequently in concentration ( 1 mg / ml ) in compared with Albendazole drug which reached for percentage ( 26.2 , 54.2 ) % when used it in the same concentration .The mice when inoculated with 1500 protoscolices in peritoneum and dosage by cisplatin and albendazole each one alone after (1,2, 3,4) months from infection.The cisplatin caused decrease in hydatid cyst number which it isolated from infected mice in contrast with the mice treatment with Albendazole which appeared number of hydatid cyst near from control group. The histological change in liver of mice treatmented with cisplatin appeared variation in inflammation response but it was less in compared with control group. The infected mice which treated with Albendazole appeared high inflammation response.The histological effects on the kidney which it was bleeding and necrosis in urinary tubules and the effects and change on the kidney increase with progress infection period.